An introduction to world Anglicanism - Kaye, Bruce (Cambridge University Press, 2008)
Who are the Anglicans? Where did they come from, and what are they up to? This Introduction to World Anglicanism will answer these questions, and on the way tell you about the foundations of their tradition, their beliefs, practices, current disputes, and why they argue so much.